Optical Packet Switching Contention Resolution Based On A Hybrid Wavelength Conversion-Fiber Delay Line Scheme - Go, Yun Ii (2004)

(untitled)
Due to the convergence of computer communication and telecommunication technology, data traffic exceeds the telephony traffic. Thus, existing connection oriented and circuit switched network will need to be upgraded toward optical packet switched network. Optical packet switching has characteristics like high speed, data rate/data format transparency and configurable. Wavelength Division Multiplexing is the technology of combining a number of wavelengths in a single fiber. It is a tremendous trend to harness larger bandwidth for enormous delivery. WDM optical devices for multiplexing and switching in simple configuration are now available at a reasonable cost. It is a very appealing solution for development of optical packet switching. The issue of contention arises when two or more packets contend for the same output port in a switch with the same wavelength, which results to packet loss. The packet loss probability is addressed as the most inevitable and significant measurable performance parameter with QoS provisioning that is dominated by wavelength contention in optical packet switches. In electronic domain packet switched network, the contention is resolved by store and forward technique using the available electronic random access memory (RAM). Due to the immaturity of optical memory storage technology, there is no available ready-to-use optical random access memory. In order to overcome this bottleneck, several approaches have been adopted to resolve the contention problem from three domains: time, space and wavelength as stated: fiber delay line (time), deflection routing (space) and wavelength conversion (wavelength). Consequently, contention resolution in wavelength domain has attracted considerable interest among the optical communications community instead of implementing optical buffering and deflection routing that have been studied previously. This thesis proposes a bufferless, single stage, non-blocking fully connected optical packet switch for synchronous optical packet switching network, followed by a prioritized scheduling algorithm in association with hybrid contention resolution schemes. This iterative prioritized scheduling comprises of a set of preemptive selective policies for contention resolution. It is a hybrid technique that integrates wavelength conversion with feedback mechanism realized by fiber delay lines (FDL). By means of simulation, the proposed scheme has been investigated and compared with the conventional baseline scheme. A sensitive description of the satisfied packet loss probability and average packet delay as a function of main design parameters such as switch size, number of wavelengths, traffic load, degree of conversion and number of fiber delay lines have been carried out with significant improvement.Simulation results proved that the proposed scheme is an efficient approach in resolving packet contention with less complexity in execution. Relatively, number of wavelength, traffic load and degree of conversion has significant impact to packet loss ratio. The implementation of fiber delay lines results on average packet delay. Simulation results demonstrated that the switch size mildly affect the performance parameter. Respectively, packet loss ratio below 10-10 is obtained via simulation by the means of wavelength conversion without conventional buffering delay. The packet loss ratio is further reduced with the method as aforementioned with the insertion of fiber delay lines where PLR below 10-13 is achieved, which is much lower than the benchmark value. Furthermore, the obtained simulation results show that by classifying packet priority, the proposed scheduling scheme and architecture are able to offer differentiated class of service.